Transformation of Indonesian Presidential Candidates’ Political Communication on TikTok in the 2024 Election - Salsabila Nirwana; Nana Abdul Aziz; Njoku Ifeanyi Daniel (Walidem Institute and Publishing, 2026)
Objective: This study analyses the transformation of the digital campaign strategy of Indonesian presidential candidates in the 2024 election by focusing on the shift in the political communication arena from the debate space and conventional media to the TikTok platform as a visual and emotion-based campaign medium. This study aims to identify the pattern of campaign strategies, political communication styles, and the level of effectiveness of candidate messages in reaching and influencing voters, especially the younger generation, through TikTok. Theoretical framework: The analysis is based on the theories of digital political communication, campaign personalisation, visual populism, and the algorithmic logic of social media as proposed by Tapsell, Kreiss, Gibson, and McAllister, as well as Lim. Literature review: The literature shows that digital campaigns in Indonesia have grown rapidly, but studies that specifically place TikTok as a strategic arena for the formation of political image, emotions, and identities in national elections are still limited. Methods: This study uses a descriptive qualitative approach with content analysis of the 30 most representative TikTok videos from the official accounts of Prabowo Subianto, Ganjar Pranowo, and Anies Baswedan during the 2024 Election campaign, accompanied by an analysis of engagement metrics as supporting data. Results: The findings show that the three candidates adopted different campaign strategies, but all submitted to the dominance of TikTok's visual-emotional logic, where Prabowo highlighted a virality-based populist-humorist style, Ganjar combined populism with the visualisation of real work, and Anies prioritised moral-intellectual communication that triggered reflective discourse. Implications: These findings confirm that the effectiveness of digital campaigns is multidimensional, involving trade-offs between viral reach and depth of political interaction. Novelty: The novelty of the research lies in the meaning of TikTok as a new political arena that actively reshapes campaign strategies, communication styles, and candidates' relationships with young voters in contemporary Indonesian electoral democracy.